Выбор сечений электрических проводов и кабелей в цепях устройств высоковольтной сильноточной импульсной техники - Баранов, Михаил Иванович (Національний технічний університет "Харківський політехнічний інститут", 2018)
Приведены результаты разработанного обобщенного электротехнического подхода к расчетному выбору по условию термической стойкости предельно допустимых сечений SCil электрических неизолированных проводов, а также изолированных проводов и кабелей с поливинилхлоридной (ПВХ), резиновой (Р) и полиэтиленовой (ПЭТ) изоляцией с медными (алюминиевыми) жилами (оболочками), по которым в цепях высоковольтной сильноточной импульсной техники (ВСИТ) протекает аксиальный импульсный ток ip(t) с произвольными амплитудно-временными параметрами (АВП). На основании данного подхода продемонстрированы результаты конкретного выбора сечений SCil для указанных электрических проводов (кабелей) силовых цепей ВСИТ с импульсным током, АВП которого с амплитудами Imp=(0,1-1000) кА изменяются по апериодическому закону или закону затухающей синусоиды в нано-, микро- и миллисекундному временных диапазонах. Представлены результаты расчетной оценки предельно допустимых плотностей δCil импульсного тока ip(t) рассматриваемых временных форм в указанных электрических проводах и кабелях силовых цепей ВСИТ. Полученные результаты будут способствовать повышению электротермической стойкости электрических неизолированных проводов, а также изолированных проводов и кабелей с ПВХ, Р и ПЭТ изоляцией, широко применяемых в силовых цепях ВСИТ.

Purpose. Implementation of calculation choice of sections of electric wires and cables in circuits of devices of high-voltage high-current impulse technique (HHIT), characterized flowing of pulsed current ip(t) with different amplitude-temporal parameters (ATP). Methodology. Electrophysics bases of technique of high-voltage and high pulsed currents, theoretical bases of the electrical engineering, bases of electrical power engineering, technique of high electric and magnetic fields, and also measuring technique. Results. The results of the developed generalized electrical engineering investigations are resulted in a calculation choice on the condition of thermal resistibility of cable products of boundary permissible sections SCil of the electric uninsulated wires, and also insulated wires and cables with copper (aluminum) cores (shells) with polyvinyl chloride (PVC), rubber (R) and polyethylene (PET) insulation, on which in the circuits of HHIT the axial-flow of pulsed current ip(t) flows with arbitrary ATP. On the basis of this approach the results of concrete choice of sections SCilare presented for the indicated electric wires (cables) of power circuits of HHIT with pulsed current, ATP of which with amplitudes of Imp=(0.1-1000) kА change on an aperiodic law or law of damped sinusoid in nanо-, micro- and millisecond temporal ranges. The results of calculation estimation present maximum permissible approximations of δCil of pulsed current ip(t) of the examined temporal shapes in the indicated electric wires and cables of power circuits of HHIT. It is shown that the values of current approximations of δCil for the uninsulated copper (aluminum) wires in the nanosecond temporal range of ATP of pulsed currents ip(t) are about 495 (293) kA/mm², in the microsecond temporal range – 26 (15) kA/mm² and in a millisecond temporal range – 543 (320) A/mm². By a calculation it is set that for the insulated wires (cables) with copper (aluminum) cores (shells) and PET with insulation the indicated current approximation of δCil is approximately: for the nanosecond range – 361 (233) kA/mm² ; for the microsecond range – 19 (12) kA/mm²; for the millisecond range – 396 (256) A/mm². Originality. Firstly by a calculation for the concrete temporal shapes of pulses of current ip(t) in the discharge circuits of HHIT, changing in the wide range of the amplitudes Imp on a aperiodic law or law of damped sinusoid, the numeral values of cross-sections SCil and current approximations of δCil are obtained for the uninsulated wires, insulated wires and cables with copper (aluminum) cores (shells) with PVC, R and PET insulation. Practical value. Application in practice of model tests of objects of electrical power engineering, aviation and space-rocket technique on resistibility to direct action of pulsed currents ip(t) with different ATP of natural (currents of lightning) and artificial (discharge currents of HHIT) origin to increase electro-thermal resistibility of the electric uninsulated wires, and also the insulated wires and cables with PVC, R and PET insulation of HHIT widely applied in power circuits.
A choice of sections of electric wires and cables in circuits of devices of high-voltage high-current impulse technique
Keywords: поперечные сечения; импульсные токи; короткое замыкание; термическая стойкость; кабельно-проводниковая продукция; изоляционные материалы; high-voltage high-current impulse technique; electric wires; electric cables